The Impact of halal awareness on trust and purchase decisions: A quantitative study of consumer behavior - Julpa, Siti; Napitu, Exsaudina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
In today's modern landscape, numerous companies are producing products labeled as halal to enhance their sales value and raise public awareness about the significance of purchasing them through religious laws. This research aims to assess the impact of Halal Awareness (HAW) on Trust (TRST) and Halal Purchase Decisions (HPD) while also highlighting the importance of Halal product usage within society. The study employs a quantitative approach with an explanatory research design, gathering data from 155 respondents who actively shop for halal products. The findings indicate a positive relationship between HAW and TRST, as well as between HAW and HPD. This suggests that a comprehensive understanding of halal product knowledge and trust can positively influence consumer perceptions of purchasing decisions. Consequently, promoting halal awareness emerges as an effective marketing strategy. At the same time, consumer trust plays a crucial role in shaping preferences for halal products.